Separation of Cd(ii) and Ni(ii) in a binary mixture through competitive adsorption and acid leaching. Issue 113 (29th October 2015) - Guo, Hong; Zhang, Shufen; Kou, Zinong; Zhai, Shangru; Ma, Wei; Yang, Yi; Huang, Yin
Abstract : Different heavy metals present simultaneously in aqueous solutions should be separated to promote environmental protection. Abstract : Different heavy metals present simultaneously in aqueous solutions should be separated to promote environmental protection. In this study, the biosorbent, succinylated maize straw, was used to separate and recover Cd(ii ) and Ni(ii ) ions from a binary mixture. The effects of various factors, such as contact time, pH, multi-metal isotherms, and adsorbent dose on the simultaneous removal of the two metal ions were investigated; a separation factor was introduced to evaluate this separation behavior. A separation process was proposed on the basis of the competitive adsorption results to separate metal ions from the binary system. This technique was then successfully employed to separate Cd(ii ) and Ni(ii ) ions from the simulated leach liquor of spent Ni–Cd batteries. Approximately 90% of the adsorbed Cd(ii ) ions were recovered, and the resulting solution contained <0.7 wt% of Cd(ii ) and >99 wt% of Ni(ii ).